Genetic basis of kernel nutritional traits during maize domestication and improvement. (7th November 2019) - Fang, Hui; Fu, Xiuyi; Wang, Yuebin; Xu, Jing; Feng, Haiying; Li, Weiya; Xu, Jieting; Jittham, Orawan; Zhang, Xuan; Zhang, Lili; Yang, Ning; Xu, Gen; et al.
Summary: The nutritional traits of maize kernels are important for human and animal nutrition, and these traits have undergone selection to meet the diverse nutritional needs of humans. However, our knowledge of the genetic basis of selecting for kernel nutritional traits is limited. Here, we identified both single and epistatic quantitative trait loci (QTLs) that contributed to the differences of oil and carotenoid traits between maize and teosinte. Over half of teosinte alleles of single QTLs increased the values of the detected oil and carotenoid traits. Based on the pleiotropism or linkage information of the identified single QTLs, we constructed a trait–locus network to help clarify the genetic basis of correlations among oil and carotenoid traits. Furthermore, the selection features and evolutionary trajectories of the genes or loci underlying variations in oil and carotenoid traits revealed that these nutritional traits produced diverse selection events during maize domestication and improvement. To illustrate more, a mutator distance–relative transposable element (TE) in intron 1 of DXS2, which encoded a rate‐limiting enzyme in the methylerythritol phosphate pathway, was identified to increase carotenoid biosynthesis by enhancing DXS2 expression. This TE occurs in the grass teosinte, and has been found to have undergone selection during maize domestication and improvement, and is almost fixed in yellow maize. Our findings not only provide important insights into evolutionary changes in nutritional traits, but also highlight the feasibility of reintroducing back into commercial agricultural germplasm those nutritionally important genes hidden in wild relatives. Significance Statement: The identification and selection‐feature characterization of genetic loci contributing to nutritional trait variation between maize and teosinte is of fundamental importance in understanding the evolutionary interface between plant and human. Most favorable alleles associated with nutritional traits exist in teosinte and are not fixed in modern maize, underscoring the potential benefit of introducing teosinte alleles during maize breeding regimens to yield hybrids with desirable nutritional traits.